Evaluation Report on Lok Karya Kshetras - Planning Commission (Planning Commission, 1967)
A great deal of emphasis has been laid in the successive Five Year Plans on the importance of securing public cooperation and participation in carrying out development programmes. Many voluntary organisations have played commendable role in this sphere and Bharat Sevak Samaj (B. S. S.) is an important one among them. The B. S. S. operates in the rural areas through the agency of public cooperation centres known as Lok Karya Kshetras (L. K. K.). The main objectives of the L. K. K. are to create social consciousness, develop local leadership and secure people’s participation in the various development programmes in rural areas. It was intended to give support to the Community Development movement in bringing about an integrated development of the rural community.
Public Cooperation Centres Programme Evaluation Organization Planning Commission Government of India